Genus Pellacalyx - a new record for flora of Vietnam - Chinh, Vu Tien; Bach, Tran The; Hai, Do Van; Quang, Bui Hong (Academia Journal of Biology, 2012)
In the world, Pellacalyx with 7-8 species distributed in China, Indonesia, Malaysia, Myanmar, Philippines, Thailand. In Vietnam, it is the first time, we confirm genus Pellacalyx distributed in Vietnam, this genus with 1 species Pellacalyx yunnanensis H. H. Hu. In Vietnam, genera Pellacalyx and Carallia are distinguished from other genera of Rhizophoraceae by living form and germination of seeds. The other genera with some important characters as “trees of inland ecosystems; seeds not germinating while attached to parent plant” and Pellacalyx and Carallia with some important characters as “trees or shrubs of coastal mangrove ecosystems; seeds germinating and hypocotyls growing from fruit while attached to parent plant”. Pellacalyx is distinguished from Carallia by some characters: Carallia: Stipules twisted, overlapping; stamens attached to disk. Pellacalyx: Stipules flat, free; stamens attached to mouth of calyx tube. We named Pellacalyx yunnanensis “Duoc bau ruou can” by two main reasons: Living form of the species is the same to Carallia -Duoc can. Calyx urceolate. Some main characters of Pellacalyx yunnanensis: Trees (3-)15 m tall. Branchlets thick, with hairs. Leave opposite or whorled, oblanceolate, oblong or lanceolate, 13-20 ´ 4.5-6.5 cm, secondary veins 8-9 pairs, base cuneate, margin serrulate, apex shortly acuminate. Pedicel ca. 2 cm, glabrous. Calyx urceolate, 6-7 lobes. Petals 6-7, white. Fruit subglobose, ca. 1.5 cm in diam. Seeds numerous, brownish black, oblong.